Moyamoya syndrome in a child with Legius syndrome: Introducing a cerebral vasculopathy to the SPRED1 phenotype?. Issue 1 (20th October 2020) - Pabst, Lisa; Carroll, Jennifer; Lo, Warren; Truxal, Kristen V.
Abstract: Legius syndrome is a disorder of the RAS and mitogen‐activated protein kinase (MAPK) pathway first described in 2007 by Eric Legius, et al., that has been considered a milder phenotype than reported in the RASopathy neurofibromatosis type 1 (NF1). However, with approximately 200 cases reported in the literature, the Legius syndrome phenotype remains to be fully characterized. We report a child who presented with moyamoya syndrome and who has Legius syndrome due to a pathogenic variant in SPRED1 . Vascular complications such as moyamoya syndrome have been reported in NF1. However, this association has not been reported in Legius syndrome. This child's case may represent an expansion of the clinical phenotype of Legius syndrome, and further study is needed. We emphasize the importance of obtaining neuroimaging studies in patients with Legius syndrome who present with new neurologic deficits.